High‐Efficiency and Stable Li−CO2 Battery Enabled by Carbon Nanotube/Carbon Nitride Heterostructured Photocathode. Issue 4 (7th December 2021) - Li, Jiaxin; Zhang, Kun; Zhao, Yang; Wang, Chuang; Wang, Lipeng; Wang, Lie; Liao, Meng; Ye, Lei; Zhang, Ye; Gao, Yue; Wang, Bingjie; Peng, Huisheng
Abstract: Li−CO2 batteries are explored as promising power systems to alleviate environmental issues and to implement space applications. However, sluggish cathode kinetics of CO2 reduction/evolution result in low round‐trip efficiency and poor cycling stability of the fabricated energy‐storage devices. Herein, we design a heterostructued photocathode comprising carbon nanotube and carbon nitride to accelerate cathode reactions of a Li−CO2 battery under illumination. Benefiting from the unique defective structure of carbon nitride and favorable interfacial charge transfer, the photocathode effectively harvests ultraviolet‐visible light to generate abundant photoexcited carriers and coordinates energetic photoelectrons/holes to participate in the discharge/charge reactions, leading to efficient photo‐energy utilization in decreasing reaction barriers and enhancing thermodynamic reversibility of Li−CO2 battery. The resulting battery delivers a high round‐trip efficiency of 98.8 % (ultralow voltage hysteresis of 0.04 V) and superior cycling stability (86.1 % efficiency retention after 100 cycles). Abstract : A carbon nanotube/carbon nitride heterostructured photocathode is designed to efficiently utilize photo‐energy to boost sluggish CO2 reduction and evolution kinetics of the Li−CO2 battery. The resulting Li−CO2 battery achieves a record‐high round‐trip efficiency of 98.8 %, superior cycling stability with high efficiency retention of 86.1 % after 100 cycles and ultrahigh areal capacity of 15.77 mAh cm −2 .